2016
DOI: 10.1177/1757975916631523
|View full text |Cite
|
Sign up to set email alerts
|

Informal processing of electronic waste at Agbogbloshie, Ghana: workers’ knowledge about associated health hazards and alternative livelihoods

Abstract: The study concludes that the low knowledge level of the workers on the hazards that are associated with their work has implications for them accepting technologies to protect them and the natural environment from contamination. It is therefore imperative for any intervention to consider the current low level of knowledge and actively educate the workers to raise their awareness level, taking into account the provision of opportunities for workers to acquire applicable skills for future employment in other fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 39 publications
3
36
1
1
Order By: Relevance
“…Surprisingly, the use of PPE was not predicted as a factor associated with risk of injury. This finding contradicted the qualitative study by Yu et al ,32 which state that use of PPE will reduce risk of injury among informal e-waste workers in Ghana. It also contradicted a study among miners where use of PPE was associated with risk of injury 33.…”
Section: Discussioncontrasting
confidence: 80%
“…Surprisingly, the use of PPE was not predicted as a factor associated with risk of injury. This finding contradicted the qualitative study by Yu et al ,32 which state that use of PPE will reduce risk of injury among informal e-waste workers in Ghana. It also contradicted a study among miners where use of PPE was associated with risk of injury 33.…”
Section: Discussioncontrasting
confidence: 80%
“…These results can be integrated into the existing literature. Burns et al and Yu et al assessed injuries among the e-waste workers at Agbogbloshie, although Burns et al focused on the role of noise exposure and Yu et al predominantly explored the health knowledge of e-waste workers [16,17,19]. Ohajinwa et al observed that cuts on hands/fingers among e-waste workers were the most common injuries [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although our study could only be a momentary snapshot, our findings should lead to clear actions. As Yu et al already stated, many of the e-waste workers do not have sufficient knowledge about the health risks of their work [19]. Occupational safety training and equipping workers with adequate tools and personal protection equipment is therefore urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 De forma coincidente con estudios previos, esta intervención tuvo un efecto mayor en conocimientos que en actitudes o prácticas. 15,16 La metodología del estudio basada en la TAS 20 permitió conocer la experiencia basal de los y las participantes, 32 diseñar estrategias adecuadas 6 y comprender, mediante el componente cualitativo, el conocimiento empírico de los sujetos que, expresado en forma de "suposición o creencia", fue transformado en conocimiento certero.…”
Section: Discussionunclassified